O potrzebie badań nad udziałem ziemiaństwa Królestwa Polskiego doby przeduwłaszczeniowej w działaniach na rzecz rozwoju przemysłu - Caban, Wiesław (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
The author asks a question about range of interest of landowners from Polish Kingdom in periods before the enfranchisement. Author makes estimated calculations from which result, that from 4000 owners possessing medium and large property, because only they could show any interest of this type of action, only about 260 landowners show activity in this area. In author’s convention key to understanding a landowner’s relations to working on things of development of industry is in their basis in the face of deeper agrarian reform, inclusive with enfranchisement. It was in a word as many followers of industrializations as followers of enfranchisement. Identification of this group may make only after carrying out wide examination, but to execute this task, it is necessary historian’s team.